Comparative risk of tuberculosis infection with different TNF-α inhibitors in immune-mediated inflammatory diseases: a systematic review and network meta-analysis - Lv, Xiuying; Liu, Yuan; Li, Yan; Zhang, Qi; Chen, Shiju; Liu, Xiaomei; Shi, Guixiu; Li, Yan (Frontiers in Immunology, 2026)
BackgroundTumor necrosis factor-α inhibitors (TNFi) are established to increase the risk of tuberculosis (TB). However, the comparative risk across different TNFi agents remains poorly defined due to a lack of head-to-head comparative studies. This network meta-analysis (NMA) aimed to evaluate and compare the risk of TB infection associated with various TNFi therapies in patients with immune-mediated inflammatory diseases (IMIDs) based on real-world, long-term cohort studies.MethodsWe conducted a systematic search of PubMed, EMBASE, Cochrane Library, and Web of Science from inception to May 30, 2025, for cohort studies reporting TB events in patients with IMIDs treated with TNFi. Study selection, data extraction, and risk of bias assessment were performed by three independent reviewers using the Newcastle-Ottawa Scale. A Bayesian arm-based NMA with random-effects models was used to estimate log risk ratio (logRR) and 95% credible intervals (CrIs) for TB infection across different TNFi agents compared with TNFi-naive.ResultsA total of 19 cohort studies involving 396, 044 patients were included. Compared to TNFi-naive, infliximab (IFX) was associated with the highest risk of TB (logRR = 2.32, 95% CrI: 1.12-3.32), followed by adalimumab (ADA) (logRR = 1.72, 95% CI: 0.42-2.65) and etanercept (ETN) (logRR = 1.39, 95% CI: 0.33-2.42). Certolizumab pegol (CZP) was associated with the lowest risk among TNFi agents.ConclusionTNFi treatment in patients with IMIDs is associated with a significantly increased risk of TB infection. Among the TNFi agents, IFX was associated with the highest risk, while ETN and CZP demonstrated lower risks. These findings can inform clinical decision-making, suggesting that ETN or CZP may be preferable in patients with high TB risk, while emphasizing that vigilant TB monitoring remains paramount regardless of the chosen agent. Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42022331674.